MODERASI BERAGAMA DI INDONESIA SEBAGAI BENTUK PENGUATAN IDENTITAS NASIONAL - Aullia, Maulida Zahra; Farah Hafidzah Hanun; Syahputra, Muhammad Akbar Al-Hafiz; Anbiya, Bakti Fatwa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
Religious moderation is an approach that prioritizes tolerance, discussion, and respect for the diversity of religious beliefs. It is important in Indonesia, as the country has many different cultures and religions. The goal of religious moderation is to maintain stability, create a strong and inclusive national identity, and prevent religious conflict. This study investigates how religious moderation helps strengthen Indonesia's national identity. The method used is a literature study by analyzing various related literature. The results show that religious moderation promotes justice, tolerance, and openness, which helps create social harmony. By accepting religious diversity and strengthening national commitment, religious moderation strengthens national identity. Implementing religious moderation is expected to create an atmosphere of inter-religious harmony in Indonesia and improve the overall quality of life of the community. Research on the religious moderation movement and its relationship with national identity needs to be conducted further to gain more information.